Bioprospecting and Structure of Fungal Endophyte Communities Found in the Brazilian Biomes, Pantanal, and Cerrado - Noriler, Sandriele A.; Savi, Daiani C.; Aluizio, Rodrigo; Palácio-Cortes, Angela M.; Possiede, Yvelise M.; Glienke, Chirlei (Frontiers in Microbiology, 2018)
Medicinal plants have been recognized as hosts of high diverse endophytic microorganisms, including fungi that produce secondary metabolites with biological activity. Two biomes in Brazil, Pantanal (wetland) and Cerrado (savannah), are known as biodiversity hotspots, and despite their importance as a reservoir for several species, knowledge about the fungal biodiversity in these biomes is very limited. Fungal endophytic communities associated with leaves and petioles of the medicinal plants Vochysia divergens (from Pantanal) and Stryphnodendron adstringens (from Cerrado) were analyzed and studied for their antimicrobial activity against human and plant pathogens. A total of 1146 isolates of endophytic fungi were obtained from plants collected in January and June of 2016 and grouped into 124 morphotypes. One isolate of each morphotype was identified by sequencing of internal transcribed spacer (ITS) region of the rDNA gene, which revealed the presence of 24 genera, including 3 possible new genera, and 48 taxa. Differences in the endophytic community according to the biomes were observed concerning the analyzed morphotypes. However, when we analyzed the diversity of genera and richness, they were similar for both plants, with Diaporthe, Phyllosticta and Neofusicoccum as dominant genera. In addition, the community composition of V. divergens differs according to the analyzed plant tissues (petiole and leaf). These data suggested that both, the plant species and plant tissues play a role in the composition of endophytic community. As regards the biotechnological potential, 5 isolates showed activity against the phytopathogens Phyllosticta citricarpa, Colletotrichum abscissum and Fusarium verticilioides, and 8 isolates showed high activity against clinical pathogens and were selected for the production of crude extract in different culture media. Extract from cultivation of Diaporthe sp. LGMF1548 and LGMF1583 and Neofusicoccum brasiliense LGMF1535 showed activity against methicillin-resistant Staphylococcus aureus, Klebssiella pneumoniae and Candida albicans. In addition, extracts of Diaporthe cf. heveae LGMF1631 inhibited 90% of the mycelial growth of the P. citricarpa and 70% of C. abscissum and may represent an alternative to be used in the biological control of these phytopathogens. Future research will focus on the chemical characterization and structural elucidation of these bioactive compounds.